Leon Siroto y Kathleen Berrin (ed.). East of the Atlantic, West of the Congo: Art from Equatorial Africa. The Dwight and Blossom Strong Collection. San Francisco: The Fine Arts Museums of San Francisco, distribuido por The University of Washington Press, 1996. 62 pp. - Varela, Hilda (Estudios de Asia y África, 2004)
-